Factors Associated With Child Health Status: A Study of Farm Families in Sabak Bernam, Selangor Darul Ehsan, Malaysia - Huang, Soo Lee (1995)
The health status of 498 children, aged 60 months and under from five villages which were stratified and randomly selected from a total of 72 in the district of Sabak Bernam was determined by birthweight, anthropometry (weight for age, height for age and weight for height) and morbidity. The main objectives of the study were to determine the health status of the children and to examine the extent to which socioeconomics, maternal factors, degree of adherence to cultural practices, feeding and illness control practices contributed to variances in health status. The study showed that the children were born with birthweights higher than the national average and they continued to develop well in their first six months after which their growth performances tended to falter. Average weight and height of these children were found to be higher than those of the Malay children of poverty villages of 1984 but lower than that of the Malay urban high income children of 1971. Generally the children had higher average height than weight achievements (compared to NCHS median). ANOVA applied to average growth performance in NCHS centile achievements showed that the infants had significantly higher growth achievements than the toddlers and preschoolers. Multiple regression analysis (significance level set at p=<0.1) found that in general, socioeconomics could explain variances in birthweight and morbidity better than anthropometry. Irrespective of age group, socioeconomics did contribute significantly to some variance in health status of the children. Maternal factors, like socioeconomics, also accounted for some of the variances in health status but its greatest contribution was to birthweight as well as to the growth performance of the infants and toddlers. There was a certain amount of pragmatic acculturation which had taken place among the families so that only during the pregnancy, birth and in child care of less than half of the children did their mothers adhere to some cultural practices. During confinement, adherence to cultural practices was highest. and food observances in accordance to the naturalistic theory of disease causation was practised by an mothers. Meanwhile adherence to culture was not found to have contributed. at the level of significance set for the study, to variances in growth performance but only to some extent in morbidity. The other two groups of factors, i.e. feeding practices and illness control did not contribute to variances in health status of infants, but by the time the child reached the toddler stage the effects of these two groups of factors on health status began to be felt and it continued into the preschooling stage. Thus from this study it would seem necessary for the Ministry of Health to give priority to toddlers and preschoolers so that the high level of health attained at birth can be maintained. This it can do by giving emphasis to educating families on proper weaning diets as well as ensuring that children are immunised as scheduled. A call is made for the Ministry of Health to work closely with other related extension agencies so that knowledge which will lead to higher status of health of infants, toddlers and preschoolers can be more effectively imparted to a wider range of rural families.